Quorum Sensing Regulates Bacterial Processes That Play a Major Role in Marine Biogeochemical Cycles - Urvoy, Marion; Labry, Claire; L’Helguen, Stéphane; Lami, Raphaël (Frontiers in Marine Science, 2022)
Bacteria play a crucial role in marine biogeochemistry by releasing, consuming and transforming organic matter. Far from being isolated entities, bacteria are involved in numerous cell–cell interactions. Among such interactions, quorum sensing (QS) allows bacteria to operate in unison, synchronizing their actions through chemical communication. This review aims to explore and synthesize our current knowledge of the involvement of QS in the regulation of bacterial processes that ultimately impact marine biogeochemical cycles. We first describe the principles of QS communication and the renewed interest in its study in marine environments. Second, we highlight that the microniches where QS is most likely to occur due to their high bacterial densities are also hotspots of bacterially mediated biogeochemical transformations. Many bacterial groups colonizing these microniches harbor various QS systems. Thereafter, we review relevant QS-regulated bacterial processes in marine environments, building on research performed in both complex marine assemblages and isolated marine bacteria. QS pathways have been shown to directly regulate organic matter degradation, carbon allocation and nutrient acquisition but also to structure the community composition by mediating colonization processes and microbial interactions. Finally, we discuss current limitations and future perspectives to better characterize the link between QS expression and the bacterial mediation of biogeochemical cycles. The picture drawn by this review highlights QS as one of the pivotal mechanisms impacting microbial composition and functions in the oceans, paving the way for future research to better constrain its impact on marine biogeochemical cycles.